Disorder of sex development associated with a novel homozygous nonsense mutation in COG6 expands the phenotypic spectrum of COG6‐CDG. Issue 4 (4th January 2021) - Lugli, Licia; Bariola, Maria Carolina; Ferri, Lorenzo; Lucaccioni, Laura; Bertucci, Emma; Cattini, Umberto; Torcetta, Francesco; Morrone, Amelia; Iughetti, Lorenzo; Berardi, Alberto
Abstract: Congenital disorders of glycosylation (CDG) are an expanding group of metabolic disorders that result from abnormal protein glycosylation. A special subgroup of CDG type II comprises defects in the Conserved Oligomeric Golgi Complex (COG). In order to further delineate the genotypic and phenotypic spectrum of COG complex defect, we describe a novel variant of COG6 gene found in homozygosity in a Moroccan patient with severe presentation of COG6‐CDG (OMIM #614576). We compared the phenotype of our patient with other previously reported COG6‐CDG cases. Common features in COG6‐CDG are facial dysmorphism, growth retardation, microcephaly, developmental disability, liver or gastrointestinal disease, recurrent infections, hypohidrosis/hyperthermia. In addition to these phenotypic features, our patient exhibited a disorder of sexual differentiation, which has rarely been reported in COG6‐CDG. We hypothesize that the severe COG6 gene mutation interferes with glycosylation of a disintegrin and metalloprotease family members, inhibiting the correct gonadal distal tip cells migration, fundamental for the genitalia morphogenesis. This report broadens the genetic and phenotypic spectrum of COG6‐CDG and provides further supportive evidence that COG6‐CDG can present as a disorder of sexual differentiation.